Well-Being - Sánchez Madrid, Nuria (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
My aim in this paper is to give an account of such a polysemic term as well-being by hand of three broad and different approaches, which will highlight the scope that the conceptual frame has to define this concept. On the one hand, I will provide a general map of some ethical approaches stemming from the philosophy of mind and the analytical address of emotions, which emphasize the subjective features of well-being, insofar as they shed light over the ties of well-being with the historicity of desire. This fact allows to affirm that the term well-being did not become an issue of social and political interest in all epochs, as it depends on an epochal configuration of subjectivity, which from the XXth century onwards claims that public institutions meet the demands aiming at achieving material satisfaction and at removing every form of exploitation and oppression. On the other hand, I will focus on the standpoint adopted by Martha C. Nussbaum, who urges that democratic societies with a liberal bottom ought to adopt emotions easing to tighten up the civil body. Thus, she argues for making of general well-being a substantive demand of practical rationality. Finally, I will focus on an overlapping approach to the analysis of Axel Honneth and Nancy Fraser, who despite their discrepancies about the predominance of recognition or redistribution share the belief that, even if well-being holds strong bounds with subjectivity, to materialize well-being requires that states avow in their policy-making a decided will to remove hunger, poverty, precarity, contempt and the different features of social oppression. Without combining all these dimensions, it will be very difficult to outline a sustainable theory about well-being, conscious of the formal and material dimensions intertwined in the tasks furthering to spread well-being in different societies, all of them framed within a neoliberal culture.
Keywords: well-being; happiness; recognition; damage; practical rationality